Прочность вертикального кожухотрубного теплообменного аппарата при сейсмическом воздействии - Кочуров, Р. Е.; Белов, С. А.; Аврамов, К. В.; Гнитько, В. И. (НТУ "ХПИ", 2011)
A strength calculations of seismically excited vertical heat exchanger are carried out. Stress-strain state of structure analyzed by using software package that implements the finite element method. Linear-spectral theory of seismic stability is used for seismic calculations.
Keywords: теплообменник; сейсмическое воздействие; вертикальный теплообменник; кожухотрубный теплообменник; математическая модель; динамическая прочность